The cultivation of amicitia, or the roots that united Luis Benjamín and Luis Fernán Cisneros with Ricardo and Clemente Palma Abrir en Google Traductor • Comentarios - Adriazola Silva, Juan Carlos (2023)
Few are the people that Don Ricardo Palma and his first-born Clemente considered as true friends, among them are Luis Benjamín Cisneros and his son Luis Fernán; brothers and children of both characters will also join this fellowship over the years. The actions, attitudes, gestures, and considerations that are reciprocally exchanged by those who consider themselves true friends have particular traits or characteristics which, according to Aristotle, are duration or transcendence in time, loyalty, the shared search for good, and happiness. Could these Aristotelian traits or characteristics be found in the relationship between the Palma and the Cisneros? Discovering this is the purpose that animates the present investigation that wishes to be a contribution to the better knowledge of the characters studied here, and whose influence is undeniable in the history, literature, and Peruvian journalism of the second half of the 19th century and the first half of the twentieth century. Keywords: Ricardo Palma, Clemente Palma, Luis Benjamín Cisneros, Luis Fernán Cisneros, Peruvian literature of the 19th and 20th centuries.